Downregulation of Stem-Loop Binding Protein by Nicotine via α7-Nicotinic Acetylcholine Receptor and Its Role in Nicotine-Induced Cell Transformation. (5th August 2022) - Sun, Qi; Chen, Danqi; Raja, Amna; Grunig, Gabriele; Zelikoff, Judith; Jin, Chunyuan
Abstract: The use of electronic-cigarettes (e-cigs) has increased substantially in recent years, particularly among the younger generations. Liquid nicotine is the main component of e-cigs. Previous studies have shown that mice exposed to e-cig aerosols developed lung adenocarcinoma and bladder hyperplasia. These findings implicated a potential role for e-cig aerosols and nicotine in cancer development, although the underlying mechanisms are not fully understood. Here we report that exposure to liquid nicotine or nicotine aerosol generated from e-cig induces downregulation of Stem-loop binding protein (SLBP) and polyadenylation of canonical histone mRNAs in human bronchial epithelial cells and in mice lungs. Canonical histone mRNAs typically do not end in a poly(A) tail and the acquisition of such a tail via depletion of SLBP has been shown to causes chromosome instability. We show that nicotine-induced SLBP depletion is reversed by an inhibitor of α7-nicotinic acetylcholine receptors (α7-nAChR) or siRNA specific for α7-nAChR, indicating a nAChR-dependent reduction of SLBP by nicotine. Moreover, PI3K/AKT pathway is activated by nicotine exposure and CK2 and probably CDK1, 2 kinases well known for their function for SLBP phosphorylation and degradation, are shown to be involved, α7-nAChR-dependently, in nicotine-induced SLBP depletion. Importantly, nicotine-induced anchorage-independent cell growth is attenuated by inhibition of α7-nAChR and is rescued by overexpression of SLBP. We propose that the SLBP depletion and polyadenylation of canonical histone mRNAs via activation of α7-nAChR and a series of downstream signal transduction pathways are critical for nicotine-induced cell transformation and potential carcinogenesis.